Measuring impact of e-learning on quality and learning outcomes: a proposal for a PhD project - Rita Falcão (2007)
In the Information Society, the term eLearning is widely used, when referring to the application of ICT to Education. This term, when analysed in a simplistic way, means "electronic learning" or learning using electronic media. However, the definition proposed by the eLearning Initiative of the European Commission, includes deeper and more complex concepts: "The use of new multimedia technologies and the Internet to improve the quality of learning by facilitating access to resources and services as well as remote exchanges and collaboration."In this definition, eLearning should include the use of multimedia technologies, and specifically, the Internet with the purpose of increasing the quality of Learning. It should also facilitate collaboration and access to resources and services.